Strategic management of regional industrial development in the aspect of space-structural transformations - D. M. Ataev; D. A. Gaynanov (Вестник университета)
The article is devoted to strategic management of regional industrial development in the conditions of spatial and structural transformations appearing in the modern economic and political environment. The article clusters Russian regions to identify groups of homogeneous territories according to the indicators of production, labour, investment, and innovation character of the industrial development. The strategic documents of the industrial development have been analysed for a number of regions from the selected clusters in the context of considering: the aspects related to spatial development in the purposes and objectives of these documents; availability of forms of spatial organisation and management of industrial and innovative activities; directions for the development of interregional cooperation; other strategic documents, including those of the municipal level. The authors have proposed as recommendations additional elements of strategising related to the spatial and structural transformations, at the stages of analysis, determination of strategic goals and priorities, tasks and specific measures of the development of the industrial complex of the region in particular, and also at the stage of determination of the mechanism for implementing the strategy and involving stakeholders in the strategic management process. Analysis of spatial disproportions, determination of the strategic goals and priorities with a focus on the spatial aspects, development of mechanisms for the strategy implementation with the involvement of municipalities contribute to the formation of a more effective and sustainable system of the industrial management which is able to adapt to changes and ensure balanced development of the region.